A semi-encapsulated PdRh alloy heterojunction for the selective catalytic hydrogenation of nitrophenylacetylene to nitrostyrene. Issue 38 (12th September 2022) - Zhang, Wenhui; Wang, Yiming; Ding, Kelong; Li, Hong; Sun, Zejun; Hu, Ze-Nan; Sun, Hong-bin
Abstract : Carbon-shell semi-encapsulated PdRh heterojunction catalysts are used for the selective semi-hydrogenation of 3-nitrophenylacetylene to 3-nitrostyrene under atmospheric hydrogen pressure. Abstract : Semi-hydrogenation usually requires an effective catalyst to ensure selectivity, especially when reducible groups coexist in a molecule. Pd is widely used in the semi-hydrogenation of alkynes to synthesize alkenes, but the selectivity control is still challenging. Herein, we design a catalyst with a semi-encapsulated PdRh alloy heterojunction in a carbon layer for the selective semi-hydrogenation of 3-nitrophenylacetylene (3-NPA). Benefiting from the presence of a PdRh alloy heterojunction and a semi-encapsulated structure, the catalyst delivers good selectivity and maintains high activity. In addition, the carbon shell can ensure the stability of the catalyst and prolong the service life. This study provides ideas for the rational design of a catalyst to achieve a selective hydrogenation reaction for practical applications.